2002
DOI: 10.1001/archotol.128.12.1377
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Reconstructive Modality on Cost of Care in Head and Neck Oncologic Surgery

Abstract: Intricate reconstructions are frequently more times consuming than primary closure, and the additional surgical procedures are more likely to use more hospital resources. Efforts at providing superior functional outcomes must be balanced against increasing restrictions on the use of health care dollars. Careful evaluation of functional outcomes and quality of life will be required to justify the increased expenditure incurred when providing complex reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 16 publications
3
31
0
3
Order By: Relevance
“…Hospital length of stay and ICU utilization were substantially increased in patients with perioperative complications. PETRUZZELLI et al concluded that intricate reconstructions are likely to involve greater utilization of hospital resrouces 14 . There was a marginal difference in length of stay between soft and bony reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital length of stay and ICU utilization were substantially increased in patients with perioperative complications. PETRUZZELLI et al concluded that intricate reconstructions are likely to involve greater utilization of hospital resrouces 14 . There was a marginal difference in length of stay between soft and bony reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…noted a cost difference in regards to reconstructive modality [21]. They found that flap closure had increases in cost and length of hospital stay when compared to primary closure [21]. Although, our study showed longer initial hospital stay (10 vs. 3 days) and higher rates of flap closures (83% vs. 55%, p = 0.003) in the SR group, there was no significant difference in initial cost ($96,163 vs. $79,216) when compared to IR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Petruzzelli et al noted a cost difference in regards to reconstructive modality [21]. They found that flap closure had increases in cost and length of hospital stay when compared to primary closure [21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Petruzzelli et al noted a cost difference in regards to reconstructive modality [21]. They found that flap closure had increases in cost and length of hospital stay when compared to primary closure [21]. Although, our study showed longer initial hospital stay (10 vs. 3 days) and higher rates of flap closures (83% vs. 55%, p = 0.003) in the SR group, there was no significant difference in initial cost ($96,163 vs. $79,216) when compared to IR.…”
Section: Discussionmentioning
confidence: 99%